Development and Investigation of Adaptive Micro-Service Architecture for Messaging Software Systems (Моделювання, керування та інформаційні технології, 2021)
Messaging Software systems (MSS) are one of the most popular tools used by huge amount of people. They could be used for personal communication and for business purposes. Building an own MSS system requires analysis of the quality attributes and considering adaptation to the changing environment. In this paper an overview of existing MSS architecture was done. Data model was developed to support historical and real time data storage and processing. An own approach to build Adaptive Microservice MSS based on the messaging middleware and NoSQL database was proposed.